The Value Distribution and Normality Criteria of a Class of Meromorphic Functions (Communications in Mathematical Research, 2020)
In this article, we use Zalcman Lemma to investigate the normal family of meromorphic functions concerning shared values, which improves some earlier related results.
Keywords: meromorphic function; shared value; normal criterion